Development in one dimension: the rapid differentiation of Dictyostelium discoideum in glass capillaries. - Bonner, J T (1995)
When Dictyostelium discoideum cells are drawn into a fine glass capillary, they rapidly begin the first steps toward the formation of prestalk and prespore zones. Some of the events occur within a minute or two, whereas others follow later. The cells in the front segment are actively motile and those in the hind segment are passive. The volumes of the segments are proportional for different-sized cell masses, and those proportions are the same as those found in normal slugs. When the cells are stained with the vital dye neutral red, the anterior zone becomes darker simultaneously with the formation of the division line. Green fluorescent protein expressed from a stalk-specific promoter is synthesized mostly in the anterior end. Later, this capillary prestalk zone shows a sharp increase in alkaline phosphatase activity, which is known to be characteristic of prestalk cells.